Um processo ágil para especificação de requisitos em programas interativos com foco em roteiros de TV - Lula., Mariana Meirelles de Mello (2011)
The addition of software to TV programs through the implantation of the Brazilian Digital TV boosted the integration of these two major industries: software and TV. These two directions have different thoughts and ways of working, however, with the release of the Digital TV these two professional, communication and information technology need to work together. The software requirements specification follows some of the activities defined in accordance with the procedure being used. In digital television requirements elicitation, we find a different environment in which there are several professional profiles involved in this activity. This research present an agile process for requirements specification in interactive programs that integrate audiovisual content and interactive applications, in order to facilitate understanding and development of the interactive program by the team involved. The approach presented is based on a screenplay and interactive user stories. The interactive script will add the interactive application information to the communication team script and the storyboard will facilitate the understanding of the application. The process was used in a real project, where twelve interactive programs were developed. Finally, we discuss the results and perspectives.